Quality of Life in Costa Rican Patients with Brain Tumors: Neuropsychological Contributions - Salazar Villanea, Mónica (2016)
The systematization of a clinical and educational experience in a hospital setting shows evidence of the neuropsychological contributions to the multidisciplinary care for patients with brain tumors. Four cases of people diagnosed with brain tumors are exemplified. The patients were treated at the Neurosurgical Unit at the Hospital Mexico, Costa Rica. Each patient underwent neuropsychological evaluations as part of the established protocol for neurosurgical interventions.Results showed a slight yet consistent trend of cognitive performance improvement after each surgery, and identified residual neurocognitive consequences that would have a direct impact on the patients quality of life. This paper discusses the challenges associated with health expectancy of prolonging life while preserving its quality and functionality.